Extraction of Flavonoids from Flavedo Layers of Citrus Fruits Peels and its Expected Anti-Diabetic and Psychological Significance; a Biochemical and Family Medicine Overview - M. I, Abdelgadir; H.M, Suliman (International Journal of Medicine, 2023)
This study was aimed at the Extraction of Flavonoids from Albedo layers of citrus fruits peels and its expected anti-diabetic significance. Lemon (Citrus limon) is the third most important species of citrus after orange and mandarin. Flavedo is the peel’s outer layer. It is a rich source of essential oils. Albedo extract was separated. Study results clearly showed the presence (p ≤ 0.05) of flavonoids in Albedo citrus layers; peel > pulp > seeds. Flavonoids are the major constituents of dry citrus fruits as well as citrus peels. Citrus fruit prevents free radical generation and reduces homocysteine level; it also possesses anti-carcinogenic, anti-diabetic, anti-inflammatory properties. Flavonoids applications in medicinal chemistry includes anticancer, antioxidant, anti-inflammatory, and antiviral properties. They also have neuroprotective and cardio-protective effects.